2002
DOI: 10.1007/s10350-004-6384-9
|View full text |Cite
|
Sign up to set email alerts
|

Value of a Protective Stoma in Low Anterior Resections for Rectal Cancer

Abstract: The particular benefit of a covering stoma is reduction in the rate of leaks requiring surgery and thus in the severe consequences of an anastomotic leakage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
117
2
21

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(151 citation statements)
references
References 28 publications
(29 reference statements)
11
117
2
21
Order By: Relevance
“…In keeping with some earlier published reports, the present study reports that males and patients who have undergone neoadjuvant chemoradiotherapy are more likely to have a defunctioning stoma at anterior resection [17,18]. In addition, the present study is also in agreement with a single study which demonstrated that stoma formation is not associated with body mass index [19].…”
Section: Discussionsupporting
confidence: 93%
“…In keeping with some earlier published reports, the present study reports that males and patients who have undergone neoadjuvant chemoradiotherapy are more likely to have a defunctioning stoma at anterior resection [17,18]. In addition, the present study is also in agreement with a single study which demonstrated that stoma formation is not associated with body mass index [19].…”
Section: Discussionsupporting
confidence: 93%
“…As some surgeons believe that "the lesser anastomotic site fecal contamination, the lesser chance of anastomotic site leakage", using diverting ileostomy or colostomy would be a constant part of their low or ultralow anterior resection [1][2][3][4][5][6][7][8]; although several recent studies have not confirmed this idea, and only persisted on less complication of the possible leakage such as the pelvic sepsis [11,19] or and less operational needs for further possible leakages [23,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Quaisquer procedimentos que eventualmente venham a ser associados às anastomoses têm poder de somar morbidades, mas não de reduzir o ín-dice de deiscência. Contudo, considerando-se os altos riscos das situações que envolvem anastomoses baixas, os pacientes do sexo masculino, os diabéticos, os fumantes ou os alcoólatras, aqueles submetidos à terapia neoadjuvante e a operações de longa duração, a profilaxia recomendável é a derivação intestinal proximal, indicada, nestes casos, para atenuar as consequências da deiscência 4,8,10,15,18,16,32,33 . O diagnóstico precoce depende, fundamentalmente, de dois fatores: primeiro, a definição pré-operatória das condições de risco e, segundo, a participação incisiva do cirurgião por um alto grau de suspeição.…”
Section: Deiscência Da Anastomoseunclassified